Exponentially reduced carrier mobility of natural ester via blocking effect of 2D hexagonal boron nitride nanosheets. Issue 2 (27th October 2020) - Huang, Zhengyong; He, Gang; Li, Jian; Wang, Feipeng; Zhang, Ruiqi; Yao, Degui
Abstract: In this work, the boron nitride (BN) nanosheets were dispersed in natural esters to fabricate the dielectric nanofluid. Microstructures and chemical compositions of the nanosized BN are determined. The stability, viscosity, and thermal conductivity of the BN nanofluid, were obtained. And the dissipation factor, electrical conductivity, and relative permittivity of the BN nanofluid, were measured. The ion mobilities and migrating times of the nanofluid were measured under different volumetric fractions of BN nanosheets and temperatures. Results show that the electrical conductivity and dissipation factor of the nanofluid decreased by 54% and 48% with the addition of only 0.1% of BN nanosheets under 110°C. Both the half‐reduced carrier mobility of the nanofluid and the declined ion concentration by blocking of BN nanosheet contributed to the exponentially reduced electrical conductivity and enhanced dielectric performances of the BN nanofluid. The suppression coefficient k is proposed to quantitatively describe the hinder effect of ion migration in nanofluids by 2D BN nanosheet. Results provide a strategy to design and develop advanced nanofluids with low‐dielectric loss by aids of surface adsorption of ion and steric hindrance of 2D nanosheets.